(untitled) (Web of Technology: Multidimensional Research Journal, 2025)
This article discusses the key aspects of developing software tools for preprocessing computed tomography (CT) images. CT images play a significant role in medical diagnostics, and preprocessing is essential to improve their quality and ensure accurate analysis. Software tools are used to enhance images, reduce noise, increase contrast, and obtain more precise results. The article covers various image processing methods, algorithms, and technical aspects of developing software tools for this purpose.